Science and technology diplomacy and the power of students: the case of Iranian student in Malaysia - Riazi, Seyed Abolhassan; Baghestan, Abbas Ghanbari; Ideris, Aini; Khaniki, Hadi; Zavare, Mehrnoosh Akhtari; Farahmand, Elaheh (Universiti Putra Malaysia Press, 2019)
The world is witnessing a paradigm shift in international relations. Due to rapid changes in science and technology, “Science and Technology Diplomacy” (scientific diplomacy) has emerged as a new strategy for developing, shaping, and reshaping international relations across the world. In this paper, a scientometric approach is applied to study the trend and progress of “Scientific Diplomacy” in Iran’s relationship with Malaysia during the last few years. The results of the study show that, with 5569 joint publications and as part of the 10,239 authors from both countries, Iranian students in Malaysia have contributed to 10.13% of Iran’s international joint publications between 2012 and 2017. Additionally, Iranian students in Malaysia have contributed to 9.8% of all Malaysian international joint publications during the same period. This is equal to 2.06% and 3.6% of all scientific publications in Iran and Malaysia, respectively. Using Malaysia as a specific case, the study shows a significant relationship between the presence of Iranian students in Malaysia and the growth of scientific and academic collaboration between the two countries. The results of the study have many scientific, political, cultural, and social implications. Considering this study and applying its results to similar cases, “Scientific Diplomacy” seems to work successfully worldwide and plays a key role in future relations among nations. “Scientific Diplomacy” has great potential for furthering the development of relations between nations in very intelligent ways, and may help their states avoid possible disputes and conflicts.